Modeling Climatic Influences on Three Parasitoids of Low-Density Spruce Budworm Populations. Part 3: Actia interrupta (Diptera: Tachinidae) - Jacques Régnière (MDPI AG, 2021)
This article is the third and last of a series of models developed to investigate the impact of climate on the spatiotemporal biology of parasitoids. After two earlier papers investigating Tranosema rostrale and Meteorus trachynotus, this last article concerns the tachinid fly Actia interrupta (Diptera: Tachinidae). An individual-based model of the seasonal biology of A. interrupta was developed to determine the impact of climate on its interactions with two of its hosts, the spruce budworm Choristoneura fumiferana (Lepidoptera: Tortricidae) and the obliquebanded leafroller C. rosaceana in eastern North America. The model is based on the developmental responses of ‘the parasitoid’s successive life stages and the ovipositional response of adult females to temperature. It was found that the number of generations this parasitoid undergoes each year varies geographically from two to four, and that its potential growth rate, as dictated by synchrony with larvae of its overwintering host C. rosaceana, is highly patterned geographically and topographically as a result of phenological matching with larvae of obliquebanded leafroller entering diapause in late summer.